TB zero plan: An integrative approach for controlling tuberculosis - Fuentes-Tafur, Luis Alberto (2012)
Introduction: We present the results of the execution of the TB zero plan, a socio-political approach that is currently being carried out in the jurisdiction of the San Cosme Health Center in La Victoria district. This is an area with a high risk for TB transmission, showing the highest incidence rates of TB in Peru, and where conditions such as informal employment, psycho-social disturbances, poverty, high migration rates, and overcrowding had hampered success of many intervention measures. The TB zero plan has been in practice since March 2009, using an integrative, systemic, and humanistic approach base don social determinants of health and primary healthcare. The plan is carried out by the local Lima City V Health Direction (DISA V, Lima Ciudad) and La Victoria Municipality, with the active participation of persons affected by TB. The plan has 6 components: political impact, clinical care of affected persons/families/communities, management of associated factors (HIV infection, psycho-social and working conditions), health and safety conditions of healthcare workers, health promotion and communication, and plan management. Within this integrative plan, the DATOS (according to its Spanish initials) strategy has been implemented (detection, analysis and socially observed therapy), which allows to strengthen the DOTS strategy in these areas with a high risk for TB transmission. Results observed are a 130% increase in the number of persons with respiratory symptoms identified, a reduction in the percentage of therapy withdrawals to 83%, a 20% reduction in the incidence of pulmonary TB, humanization of family/community healthcare, and the participation of local authorities in the design and execution of health public policies. We suggest to apply this model in other areas with a high risk for Tb transmission in this country and/or elsewhere.